Die Lage der Fischbestände in Nordostatlantik, Nord- und Ostsee. Einschätzungen des Internationalen Rates für Meeresforschung im Frühjahr 2001 - Gröhsler, Tomas; Zimmermann, Christopher (2001)
The spring session of ACFM gave advice for a number of stocks in the North Atlantic, North Sea and Baltic. The present assessment of the situation is given here for stocks of importance for the German fishery. These are: Blue Whiting: the stock size is rapidly decreasing due to high catches; ICES recommends a closure of the fishery. Herring (Atlanto-Scandian, Norwegian spring spawner): Stock is within save biological limits, weak recruitment of the recent years will lead to a further reduction of biomass. Herring (North Sea): revision of the assessment led to a different perception of the stock: SSB was in 2000 below Blim. Excellent recruitment will lead to an increase of SSB over Blim within this year, but ICES recommends to reduce fishing mortality on adults significantly. Herring (Baltic spring spawner in 22–24, IIIa): Still no increasing tendency is detectable. Herring (VIaNorth): stable. Redfish: generally further decreasing tendency observed, a reduction of the fishery is recommended. Signs of recovery visible only for two units. Greenland Halibut: State of the stock not quite clear, but slightly positive tendencies. The present fishing intensity should be reduced. Cod (Kattegat): Weak recruitment, outside safe biological limits. ICES recommends a closure of the fishery. Cod (22–24, Western Baltic): Stock situation unclear due to extensive migrations. F should be reduced by at least 10%.